Getting my child to eat the right amount. Mothers' considerations when deciding how much food to offer their child at a meal. (1st May 2015) - Johnson, Susan L.; Goodell, L. Suzanne; Williams, Kimberly; Power, Thomas G.; Hughes, Sheryl O.
Highlights: Mothers' decisions about children's portions consider the child's food preferences. Portion sizes differ for "good" eaters and "picky" eaters. Mothers have emotional investments in their child's consumption. Fruit is thought of as dessert and is used instrumentally to alter children's eating. Abstract: Feeding young children successfully requires parenting skills, trust that children will eat, and nutrition and child development knowledge to ensure that foods and the amounts offered are developmentally appropriate. Mothers are often responsible for determining how much food is offered to their children; however, the influences on mothers' decisions regarding how much to offer their children – their motivations, goals for feeding and child consumption – have not been investigated. Study aims included gathering qualitative data regarding mothers' decisional processes related to preparing a dinner meal plate for her preschooler. Low income mothers (n = 15 African American and n = 15 Latina mothers) were recruited from preschools in the Denver, CO metropolitan area to participate in semi-structured interviews. Mothers prepared a plate for their preschooler and were asked about influences on their decisions about portion sizes and their expectations for children's eating. Data were coded by 2 independent coders using a consensus coding process and analyzed by investigators. Three themes emerged: (1) portion sizes differ for children who are "good" eaters and "picky" eaters; (2) mothers know the "right amounts" to serve their child; and (3) mothers have emotional investments in their children's eating. Some influencing factors were child-centered (e.g. child's likes and dislikes, "picky" and "good" eaters, and foods previously eaten in the day) and some related to adult expectations and concerns (nutrient content and waste). Interventions focusing on portion size may be more effective if tailored to the mothers' perceptions regarding her child's eating characteristics.